3D Conformal Radiotherapy in Cervical Metastasis to Brain - R. K. Minyazeva; G. Yu. Battalova; I. V. Sakhautdinova; I. M. Tayupova; I. R. Gilyazova (Креативная хирургия и онкология, 2022)
Background. Cervical cancer is among the commonest malignancies and a top fourth leading cause of cancer death in women worldwide. The five-year survival rate in locally advanced cervical cancer is 91.5%, and only 17.2% — in distant metastasis. Primary cervical cancer metastasis to brain is very rare. Report and analysis of quite rare clinical cases may shed light on this issue, helping formulate relevant therapeutic and diagnostic interventions.Materials and methods. The article describes a case of cervical cancer metastasis to brain. The patient received modern 3D conformal intensity-modulated (IMRT) and image-guided (IGRT) radiation therapies on an Elekta Synergy highenergy linear digital accelerator instrument.Results. Clinical effect has been achieved by end of treatment. Time since diagnosis of primary cervical cancer was 13 months, and 7 months — since diagnosis of brain metastasis.Discussion. The survival rate in brain metastasis is marginal-low and depends on the patient’s age, primary tumour state, presence of extracranial metastases, as well as volume, number and location of metastases in brain parenchyma. An integrated approach including surgery, radiation and chemotherapy is considered superior to improve survival and the quality of life.Conclusion. Despite sheer coverage of therapies available, the mean survival rate in intracranial metastasis remains subtle. Thereby, research and discovery of relapse and metastasis biomarkers of cervical cancer is relevant.